Current-injected photovoltaic array for concentrated space solar power station - Li, Xintong; Mi, Jianwei; Zhang, Yiqun; Chen, Guangda; Fan, Guanheng; Wang, Dongxu; Du, Yingchun (Frontiers in Energy Research, 2023)
In this paper, the power generation of a concentrated space solar power station (SSPS) is enhanced by a current-injected total-cross-tied (TCT-CI) photovoltaic (PV) array. First, a mathematical model of the TCT-CI connected PV array is established. Second, PV arrays with several common topologies and TCT-CI topology are simulated and analyzed in MATLAB/Simulink. At last, comparative experiments were conducted for TCT and TCT-CI connected PV arrays under the condition of non-uniform light intensity distribution was carried out. The above results indicate the following: 1) The TCT-CI connected PV array reduces the difficulty of MPPT in the concentrated SSPS. 2) The TCT-CI connected PV array increases the power generated in the concentrated SSPS. 3) The TCT-CI connected PV array is applicable for the concentrated SSPS.